2002
DOI: 10.5980/jpnjurol1989.93.463
|View full text |Cite
|
Sign up to set email alerts
|

Impact of a Clinical Pathway in Cases of Transurethral Resection of the Prostate

Abstract: With the implementation of the clinical care pathway, average hospital charges and length of stay were reduced. The clinical pathway program is considered to be a good tool for health care cost management. This methodology can be applied to all patients. However, when we make the clinical pathway program, we take into account the individuality of each patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(33 citation statements)
references
References 0 publications
0
33
0
Order By: Relevance
“…. Thirty‐eight eligible studies with relevant outcomes were found, including two quasi‐randomized studies. In total 67 papers on these studies were reviewed ( Appendix S1 , supporting information).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…. Thirty‐eight eligible studies with relevant outcomes were found, including two quasi‐randomized studies. In total 67 papers on these studies were reviewed ( Appendix S1 , supporting information).…”
Section: Resultsmentioning
confidence: 99%
“…Two studies on patients undergoing colorectal surgery included both open and laparoscopic procedures, and reported separate results; these were entered as separate study populations in the meta‐analyses. There were ten non‐English language papers: eight in Chinese, one in Japanese and one in German. Two studies were reported in abstract form only.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations